A Literary Approach to teaching English Language in a Multi - Cultural Class - Room - Sanju Choudhary (Laureate Education Inc, 2016)
Literature is not generally considered as a coherent branch of the curriculum in relation to language - development in either mother tongue or foreign language - teaching. As teachers of English in Multi cultural Indian class rooms we come across students with varying degree of competence in English language learning. Though, language learning is a natural process for natives but the Students of other languages put in colossal efforts to learn it. Despite   their sincere efforts they face challenges regarding Pronunciation, Spelling and Vocabulary. The Indian class rooms are a microcosm of the larger society, so teaching English language in a manner which equips the students to face the cut-throat competition has become a necessity and a challenge for English language Teachers. English today has become the key determinant for getting success in their career. The hackneyed and stereotypical methods of teaching are not acceptable now. Teachers have no longer remained arbitrary dispensers of knowledge but they are playing the role of a guide and facilitator for the students. Teachers of English are using innovative ideas to make English language teaching and learning interesting and simple. Teachers have started using the literary texts and their analysis to explore and ignite the imagination and creative skills of the students. One needs to think and rethink the contribution of literature to intelligent thinking as well as its role in the process of teaching - learning. My paper would, therefore, be an attempt at exploring the nature of the literary experience in the present day class rooms; and the broader role of literature in life.